2008
DOI: 10.1021/nl0730155
|View full text |Cite
|
Sign up to set email alerts
|

A Nano-Combinatorial Library Strategy for the Discovery of Nanotubes with Reduced Protein-Binding, Cytotoxicity, and Immune Response

Abstract: We have discovered functionalized multiwalled carbon nanotubes with reduced protein-binding, cytotoxicity, and immune response and the associated structure-activity relationships using in silico surface molecular diversity design, combinatorial library synthesis, and multiple biological screenings. Our results demonstrated the general utility of the nanocombinatorial library approach in nanomedicine and nanotoxicity research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
195
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(202 citation statements)
references
References 51 publications
(82 reference statements)
4
195
0
2
Order By: Relevance
“…They compared the InfaRed (IR) spectra with several descriptors commonly used in (Q)SAR studies and found that IR spectra carries unique information which cannot be obtained from molecular descriptors. (Zhou, et al, 2008) used the spectra of MWNTs for characterization purposes while (Y. Yang, Guo, Hu, Wang, & Wang, 2004) attempted to link XRD data to photocatalytic performance tested by dye decolourisation rate.…”
Section: Np-specific Descriptorsmentioning
confidence: 99%
“…They compared the InfaRed (IR) spectra with several descriptors commonly used in (Q)SAR studies and found that IR spectra carries unique information which cannot be obtained from molecular descriptors. (Zhou, et al, 2008) used the spectra of MWNTs for characterization purposes while (Y. Yang, Guo, Hu, Wang, & Wang, 2004) attempted to link XRD data to photocatalytic performance tested by dye decolourisation rate.…”
Section: Np-specific Descriptorsmentioning
confidence: 99%
“…[ 33 ] For animal experiments, the suspensions of f-MWCNTs were prepared in PBS with 1% Tween 80 and sonicated for 1 h to facilitate dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…[ 33 ] To test the effects of this combinatorial f-MWCNT library, which contains 80 members, on CYP3A4 activity in a high-throughput format, we determined the remaining parent drug concentration after incubating library members with NFP in HLM. As shown in Figure 5 , multiple f-MWCNTs with diverse chemistries modulated the enzymatic activity of CYP3A4 over a broad range (60%-131%).…”
Section: Mwcnt Surface Chemistry Affects the Functional Regulation Ofmentioning
confidence: 99%
“…In 2008, Zhou et al created a library containing 80 multi-walled nanotubes (MWNTs) with known biological activities [35]. They tested the toxicity of these decorated nanotubes using six different toxicity endpoints (four protein binding activities, cell viability and nitrogen oxide generation).…”
Section:  Sample Sizementioning
confidence: 99%
“…They also revealed the structure-activity relationship between the type of building block and the biocompatibility. The raw data generated by Zhou et al [35] have been assessed below to find out their suitability for developing nano-(Q)SAR models: Their complete dataset is summarized in Table-S5. They attempted to perform multivariate linear regression (MLR) and linear discriminant analysis (LDA) classification techniques on the collected dataset.…”
Section:  Sample Sizementioning
confidence: 99%